Human resource development : from theory into practice - Sadler-Smith, Eugene (London: Sage publications, 2022)
"Human Resource Development: From Theory into Practice is an essential resource for students working towards a career in human resource development (HRD), human resource management (HRM), occupational and organizational psychology, and related areas of business management and organization. Key features : Aligns with the CIPD Professional Standards and the CIPD's Level 7 Diploma in Learning and Development. Covers all the fundamentals of HRD theory and practice, along with cutting-edge topics such as the e-learning, 'hybrid learning', neuroscience and learning, 'learning ecosystems', and the 'new learning organization'. Follows a unique framework based on the a distinction between 'micro-HRD', which zooms-in on the fine detail, and 'macro-HRD', which zooms-out to look at the bigger picture. Includes a rich array of research insights, case studies and examples from a variety of contexts"--
Part I: Micro-HRD -- 1: Setting the scene for human resource development (HRD) -- 2: Inside the 'black box' -- 3: Learning from and with others -- 4: Experience-based modalities of learning -- 5: 'Neurolearning and HRD -- 6: Formal and informal learning -- 7: Maximizing employees' potential -- Part II: Macro-HRD -- 8: The bigger picture -- 9: HRD as a strategic partner -- 10: The HRD system -- 11: Hybrid HRD -- 12: Does HRD cost or pay? -- 13: The only sustainable source of competitive advantage -- 14: Knowledge and the new learning organization.
Includes bibliographical references (pages 413-450) and index.
Keywords: Personnel management; Personnel -- Direction; Personnel management